Prevalence of Dementia Among Eldery in Panti Werdha Budi Mulia Jelambar - Ingkiriwang, Elly; Andri, Andri; Salikur, Salikur; R, Meiliana Lindawaty; Veronica, Veronica (Universitas Kristen Krida Wacana, 2023)
Dementia is a degenerative disease that many people have to faced, especially the elderly in theworld. In Indonesia, the number of elderly increases over time. Dementia is defined as a clinicalsyndrome resulting in loss of intellectual functions, especially memory that can affect everyday life.The purpose of this study was to determine the prevalence of dementia in the elderly in Panti BudiMulia Werdha Jelambar. The method in this research use descriptive research method with crosssectional study design. The samples in this study using total sampling with inclusion and exclusioncriteria. The total sample of 73 respondents. The study was conducted using Mini Mental StatusExamination (MMSE) questionnaires. The result showed the lower the education level of therespondent, the higher the risk of dementia, and women at high risk for dementia Marital status alsoaffects the incidence of dementia. Diseases such as diabetes mellitus, hypertension, and stroke alsoaffect the occurrence of dementia. 47,9% of respondents suffering from dementia, 38,4% had thepossibility of cognitive impairment, and 13,7% of respondents did not developed dementia.